Management of Calvarial Osteoradionecrosis After Treatment of Cutaneous Malignancy: A Systematic Review - Pang, Siyuan; Concannon, Elizabeth; Higgins, Martin; Drummond, Katharine; Gearing, Peter; Devine, Maxim; Tiong, Albert; Ramakrishnan, Anand; Fox, Carly (Otolaryngology-head and neck surgery, 2025)
Objective Osteoradionecrosis (ORN) is a recognized complication of radiotherapy. However, calvarial ORN (ORNC) following treatment for cutaneous malignancies is poorly understood. Shedding light on the limited evidence to date, this study aims to summarize existing evidence and highlight the research gaps. Data Sources PubMed and Embase. Review Methods A systematic search of PubMed and Embase was conducted up to May 2024, using relevant keywords to identify papers on ORNC. Data on the definition, incidence, risk factors, radiotherapy parameters, diagnostic methods, and management strategies were collected. Results Twenty articles reporting on 42 ORNC patients were identified, revealing relatively poor data quality. There remains no consensus on a definition of ORNC. Patient‐ and disease‐related risk factors have been inconsistently documented. No conclusion could be reached regarding thresholds for radiation dose delivery, as only seven studies reported the total radiation dose, with a mean of 58.9 Gy. Twenty‐five (60%) cases managed with wound care and antibiotics demonstrated a spectrum of success rates, while 90% of surgically managed ORNC wounds healed at various follow‐up points, ranging from 6 weeks to 9 years. Conclusion This study proposes an ORNC‐specific definition and reporting standard through comparison with mandibular ORN. This will help generate valuable data, guiding the development of an ORNC‐specific treatment protocol and clinical decision‐making in managing this debilitating side effect of radiotherapy.